2016
DOI: 10.1103/physrevd.94.023501
|View full text |Cite
|
Sign up to set email alerts
|

Circular polarization of the CMB: Foregrounds and detection prospects

Abstract: The cosmic microwave background (CMB) is one of the finest probes of cosmology. Its all-sky temperature and linear polarization fluctuations have been measured precisely at a level of δT=T CMB ∼ 10 −6 . In contrast, circular polarization (CP) of the CMB has not been precisely explored. The current upper limit on the CP of the CMB is at a level of δV=T CMB ∼ 10 −4 and is limited on large scales. Some of the cosmologically important sources which can induce a CP in the CMB include early Universe symmetry breakin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 81 publications
(136 reference statements)
0
45
0
Order By: Relevance
“…We expect this ratio to increase with ν −0.5 , approaching 10 −3 at 40 MHz, which might be a detectable level for current instrumentation [45]. The frequency scaling of V /I ∝ ν −0.5 was already predicted by [36] for the GHz range.…”
Section: Predictionmentioning
confidence: 50%
See 1 more Smart Citation
“…We expect this ratio to increase with ν −0.5 , approaching 10 −3 at 40 MHz, which might be a detectable level for current instrumentation [45]. The frequency scaling of V /I ∝ ν −0.5 was already predicted by [36] for the GHz range.…”
Section: Predictionmentioning
confidence: 50%
“…Nevertheless, the provided CP prediction can be used for template based searches for the elusive CP signal. Our model shows similarities and differences to a CP prediction based on a 3D models of the Milky Way [36]. We expect our model to capture more details of the real CP sky, as its construction is based directly on observed data sets, without the detour of using those to construct a parametrized, and therefore coarse, 3D model.…”
Section: Detection Strategy a Traditional Imagingmentioning
confidence: 74%
“…King & Lubin (2016) suggest that 3.4 n -is a reasonable model for synchrotron circular polarization. With this source spectrum, SPIDERʼs circular polarization limits in Figure 4 scale by 0.08 at 95 GHz and 0.11 at 150 GHz, still using CMB temperature units.…”
Section: Resultsmentioning
confidence: 99%
“…Additional sources include postulated extensions to QED such as Lorentz-invariance violating operators (Colladay & Kosteleckỳ1998;Alexander et al 2009), axion-like pseudoscalar particles (Finelli & Galaverni 2009), and nonlinear photon interactions (through effective EulerHeisenberg Lagrangians; Motie & Xue 2012). A brief review of some of these generation mechanisms can be found in King & Lubin (2016). Despite the wide range of physical processes they invoke, all of these mechanisms predict levels of circular polarization that are unlikely to be accessible with current technology.…”
Section: Introductionmentioning
confidence: 99%
“…In astrophysics, circular polarization may arise in masers [6,7], gamma-ray-burst afterglows [8][9][10][11], jets of active galactic nuclei [12][13][14][15], and pulsars [16][17][18][19]. In addition, circular polarization has recently been discussed also in the context of the CMB [20][21][22][23][24][25]. Circular polarization can be produced through Faraday conversion when a linearly polarized light ray propagates through a medium where the indexes of refraction differ along the two different transverse axes.…”
Section: Introductionmentioning
confidence: 99%